On the predictability of supramolecular interactions in molecular cocrystals – the view from the bench. Issue 29 (16th June 2016) - Corpinot, Mérina K.; Stratford, Samuel A.; Arhangelskis, Mihails; Anka-Lufford, Jodie; Halasz, Ivan; Judaš, Nenad; Jones, William; Bučar, Dejan-Krešimir
Abstract : A series of cocrystals involving theophylline and fluorobenzoic acids highlights the difficulty of predicting supramolecular interactions in molecular crystals. Abstract : A series of theophylline cocrystals involving fluorobenzoic acids was prepared and structurally characterised. The cocrystals display compositions and hydrogen-bond patterns that could not be predicted based on extensive literature/database surveys and the use of other tools. The study demonstrates that – without the use of first-principles crystal structure prediction methods – it is still remarkably difficult to predict and understand the outcomes of cocrystallisation attempts involving small and rigid molecules.